Increased FUN14 domain containing 1 (FUNDC1) ubiquitination level inhibits mitophagy and alleviates the injury in hypoxia-induced trophoblast cells - GuoQing Chen (Taylor & Francis Group, 2021)
Preeclampsia (PE) is a pregnancy disorder characterized by excessive trophoblast cell death. This study aims to explore the exact mechanism of the ubiquitination level of FUN14 domain containing 1 (FUNDC1) in mitophagy and injury in hypoxic trophoblast cells. In this study, HTR-8/SVneo trophoblast cells were cultured under normoxic and hypoxic conditions and PE mouse model was established. We found low ubiquitination level of FUNDC1 in hypoxic trophoblast cells and placenta of pregnant women with PE. Proteasome inhibitor MG-132 and protease activator MF-094 were added into HTR-8/SVneo trophoblast cells. Proteasome inhibitor MG-132 decreased FUNDC1 ubiquitination level while protease activator MF-094 increased FUNDC1 ubiquitination level. Inhibition of FUNDC1 ubiquitination promoted mitophagy and mitochondrial membrane potential (Δψm) in normoxic trophoblast cells, increased levels of reactive oxygen species (ROS) and malondialdehyde (MDA) and decreased levels of glutathione (GSH) and superoxide dismutase (SOD). In addition, FUNDC1 ubiquitination alleviated cell injury in PE mice in vivo. In conclusion, increased FUNDC1 ubiquitination level inhibited mitophagy and Δψm changes in hypoxic trophoblast cells, and thus alleviated oxidative injury.